COMPARATIVE STUDY OF AR & VR IMPLEMENTATION IN ARCHITECTURAL DESIGN - Redyantanu, Brasmata Putra (Border: Jurnal Arsitektur, 2020)
Architectural design is a process of creating built environment, to achieve certain goals. Within the process, there are several steps of design, start from conceptual design, technical drawing, until the construction stage. Architect needs to present their idea to client, to reach an agreement on building design. Architect can use old school technic to communicate their idea, such as manual drawing, scale model, animation, but also the recent technology such as Augmented Reality and Virtual Reality. This study seeks to find the character of the use of each of these technologies through literature study, make comparisons, and conclude each character so that architectural designers can use these media appropriately in their design process.